Uncertainties in the Management of a Lynch Syndrome Patient: A Case Report - Campos,Sara (2017)
Introduction: Lynch syndrome (LS), the most common hereditary colorectal cancer syndrome, is characterized by mutations in mismatch repair (MMR) genes leading to an increased cancer risk, namely colorectal cancer. Case: In the context of surveillance colonoscopy, a 40-mm flat lesion (0-IIa+b, Paris classification) was identified and submitted to piecemeal mucosal endoscopic resection in a 64-year-old LS patient with an MLH1 germline mutation (262delATC) and two previous segmental resections due to metachronous colorectal cancer. Pathology raised the suspicion of superficial submucosal invasive carcinoma with poor differentiation. Immunochemistry showed heterogeneous MLH1 expression and PMS2 loss. In a short-term follow-up colonoscopy, another 30-mm advanced carcinoma was identified. The patient was referred to surgery. Conclusion: This case raises several issues: (1) the potentially fast tumorigenesis and progression to carcinoma in LS and implications for endoscopic screening and surveillance; (2) pitfalls in the interpretation of MMR proteins immunochemistry; (3) the role of endoscopic resection in LS.